Respostas
respondido por:
0
Resposta:
Explicação passo-a-passo:
a2= 9 e a14 = 45 a1 + 13r = 45 a1 + r = 9(-1) a1 + 13r = 45 -a1 - r = -9 12r = 36 r = 3.
respondido por:
1
Boa tarde!
→Vamos responder utilizando um método bem simples:
Tf-Ti → 14-2 = 12
Vf-Vi → 45-9 = 36
Razão → 36/12 = 3
_______________
Tf →Termo Final
Ti → Termo Inicial
Vf → Valor final
Vi → Valor inicial
_______________
Att;Guilherme Lima
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás